Ataxin-3, The Spinocerebellar Ataxia Type 3 Neurodegenerative Disorder Protein, Affects Mast Cell Functions - Sowa, Anna S.; Haas, Eva; Hübener-Schmid, Jeannette; Lorentz, Axel (Frontiers in Immunology, 2022)
Spinocerebellar ataxia type 3 (SCA3), also known as Machado-Joseph Disease, is a progressive neurodegenerative disorder characterized by loss of neuronal matter due to the expansion of the CAG repeat in the ATXN3/MJD1 gene and subsequent ataxin-3 protein. Although the underlying pathogenic protein expansion has been known for more than 20 years, the complexity of its effects is still under exploration. The ataxin-3 protein in its expanded form is known to aggregate and disrupt cellular processes in neuronal tissue but the role of the protein on populations of immune cells is unknown. Recently, mast cells have emerged as potential key players in neuroinflammation and neurodegeneration. Here, we examined the mast cell-related effects of ataxin-3 expansion in the brain tissues of 304Q ataxin-3 knock-in mice and SCA3 patients. We also established cultures of mast cells from the 304Q knock-in mice and examined the effects of 304Q ataxin-3 on the immune responses of these cells and on markers involved in mast cell growth, development and function. Specifically, our results point to a role for expanded ataxin-3 in suppression of mast cell marker CD117/c-Kit, pro-inflammatory cytokine TNF-α and NF-κB inhibitor IκBα along with an increased expression of the granulocyte-attracting chemokine CXCL1. These results are the beginning of a more holistic understanding of ataxin-3 and could point to the development of novel therapeutic targets which act on inflammation to mitigate symptoms of SCA3.